Case reportsIncomplete pentalogy of Cantrell: a case report - Gunay, Celalettin; Cingoz, Faruk; Yesil, Fahri Gurkan; Guler, Adem; Celik, Turgay (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
Adult congenital heart defects, including atrial septal defect (ASD), may be associated with various anomalies [1]. This report presents the case of a patient with ASD, who was also diagnosed with pentalogy of Cantrell, a rare multiple congenital malformation syndrome characterized by a combination of features: a midline supraumbilical abdominal wall defect, a defect of the lower sternum, a defect of the diaphragmatic pericardium, deficiency of the anterior diaphragm, and congenital cardiac anomalies [2]. Our patient demonstrated an incomplete form of pentalogy of Cantrell, which is very rare. In our case, the “abdominal wall defect” and “deficiency of the anterior diaphragm” components of pentalogy of Cantrell were absent.